Analysis of the performance of national teams in Greco-Roman wrestling at the European Nations Cup 2014 - Тропін Юрій Миколайович (Yurii Tropin); Пономарьов Віктор Олександрович Viktor Ponomaryov; Кліменко Олег Іванович (Oleg Klemenko) (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: to analyze the performance of national teams in Greco-Roman wrestling at the European Nations Cup in 2014. Material and Methods: the analysis of 69 wrestlers highly Greco-Roman style. Results: 10 basic technical actions that is most more often used by wrestlers. Analysis of competitive activity wrestlers Greco-Roman style on the KEN-2014 showed that more technical actions carried out in the front – 117 receptions than on the ground – 87 receptions. Conclusions: it was found that in the competitive technology dominated the offensive, the fight is ongoing at a fast pace, techniques are performed after prior training and if the athlete is confident that the reception will be executed.